STRATEGIES FOR OPTIMIZING THE "EKSUS SMART" APPLICATION FOR THE COMMUNITY TO INCREASE TRANSPARENCY IN THE PERFORMANCE OF INVESTIGATORS IN HANDLING CRIMINAL ACTS - Hiroyuki Aditya Siburian; Riska Sri Handayani; Lin Yola (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2024)
The Indonesian National Police (POLRI) confront a myriad of challenges in criminal investigations, contending with dynamic crime scenes and the need for prompt decision-making. Police Chief Listyo Sigit Prabowo leads the charge in operational transformation through the 6th program, the POLRI Transformation Road Map, focusing on elevating law enforcement performance. At the core of this initiative is the "EKSUS SMART" application, developed to streamline investigations. While holding promise for enhancing POLRI investigators' performance, practical obstacles necessitating optimization have emerged. This study aims to evaluate the utilization of "EKSUS SMART" in criminal investigations by POLRI investigators, proposing strategies to boost public participation in reporting crimes. Optimization goals encompass efficiency, effectiveness, and transparency in crime handling, coupled with fostering public trust in law enforcement. Employing qualitative research and drawing on theories like Diffusion of Innovation (DOI) and the Technology Acceptance Model (TAM), the study underscores the intricate nature of criminal case management, requiring high levels of expertise and professionalism. While "EKSUS SMART" contributes positively to efficiency and transparency, resolving technical, legal, and social challenges is crucial for its optimal application in upholding public safety. Specific optimization strategies, including heightened public awareness, user-friendly design, and instilling trust in reporting processes, are deemed essential. Improvements in investigator services, training, and communication skills are identified, along with the need for enhanced coordination and collaboration among investigators, government, and the public, achievable through improved information infrastructure and increased public interest in transparency and investigations.